Virtual Worlds, Digital Dreams - Šisler, Vít (Digital Middle East: state and society in the information age, 2018)
Video games are inherently transnational by virtue of their industrial, textual and player practices. Until recently, the focus of research on the social and cultural aspects of video games has been on the traditional centers of the video game industry consumption, while the international flows of digital gaming remained largely underexplored. This chapter analyzes the cultural dynamics and technological processes influencing both video game development and the gaming culture in the Middle East. It conceptualizes Middle Eastern video games as imaginary spaces that entangle diverse and contradictory processes: global cultural flows, media policies of nation states, visions and engagements of private entrepreneurs, and migration and appropriation of Western game genres and rule systems. By mapping out dominant trends, the chapter offers the opportunity to think about processes and flows influencing the video game industry in the Middle East during the first fifteen years of its existence
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé